Steroidogenic, Metabolic, and Immunological Markers in Dairy Cows Diagnosed With Cystic Ovarian Follicles at Early and Mid-Late Lactation - Lima, Fabio S.; Acosta, Diego A. V.; Egan, Tonja R.; Skenandore, Cassandra; Sulzberger, Saige; French, Dennis D.; Cardoso, Felipe C. (Frontiers in Veterinary Science, 2019)
Cystic ovarian follicles (COF) etiology remains a conundrum with steroidogenic, immunological, and metabolic dysfunctions linked to its development. Studies suggest that COF development may occur as a result of disruption of the insulin signaling pathway and the severity of negative energy balance in dairy cows, but mid to late lactation cows diagnosed with COF are unlikely to have issues with energy metabolism. Herein, we characterized the mRNA expression of steroidogenic (LHCGR, StAR, CYP11A1, 3β-HSD, CYP19A), immunological (IL-1β, IL-6, IL-8, TLR-4, TNF), and metabolic markers (IGF-1, IRS1) in follicular fluid; and plasma and follicular fluid levels of E2, IL-1β, glucose, and NEFA in early and mid-late lactation COF cows. Lactating dairy cows were diagnosed as COF (n = 11, follicle > 20 mm persistent for seven days, absence of corpus luteum, and flaccid uterus) while 11 herdmates cycling with a dominant follicle were classified as Control. Cows diagnosed with COF were classified as early lactation (COF-E, n = 5), < 35 days in milk (DIM); or mid-late lactation (COF-M/L, n = 6), ≥ 118 DIM. Results revealed that mRNA expression StAR was greater (P < 0.01) in COF-E than COF-M/L and Control. The mRNA expression CYP19A1 was lower (P < 0.01) in COF-E and COF-M/L than Control cows. The mRNA expression IL-6 and IRS-1 tended to be greater and lower, respectively, in COF-M/L than Control. The mRNA expression IGF-1 was greater (P < 0.01) in COF-E and COF-M/L than in Control cows. The plasma and follicular fluid concentration of NEFA was greater (P < 0.05) in COF-E than COF-M/L and Control. Cows with COF-E had disturbances in steroidogenic and metabolic markers, while cows with COF-M/L had steroidogenic, immunological, and metabolic dysregulations suggesting that COF pathogenesis may vary between early and mid-late lactation dairy cows.